A Study of Generation Y’s Perception towards Chinese Smartphone Brands - Goh, Li Jie (2019)
Chinese smartphones brands are currently rising and expanding their international market. Currently, Generation Y who are tech-savvy and rely more on technical devices than other generations are the largest buyer of smartphones in Malaysia. The main objectives of this research is to determine the factors influencing the purchasing intention towards Chinese brands smartphones. Based on literature reviews, this study finds five factors that influence Chinese brand smartphones purchasing intention namely perceived usefulness, perceived ease of use, price, social influence and perceived quality. This research used a questionnaire with a 5-point Likert scale for data collection and a sample of 150 Generation Y respondents from the Klang Valley region of Malaysia. It is found that only social influence and perceived quality have significant impacts on the Chinese brands smartphones purchasing intentions. Other factors such as perceived usefulness ,perceived ease of use and price are statistically insignificant. Hence, marketers in the smartphones industry, specifically in the Chinese smartphone market can consider these factors to assess and help improve their sales.